APPROACHES TO STAFF BEHAVIOUR FROM THE PERSPECTIVE OF OPERATIONS MANAGEMENT - CRETOIU, Raluca (Annals of Spiru Haret University. Economic Series, 2019)
Operational management or operations management, as established in many speciality papers, is an area of activity that is particularly important for the successful implementation of business activities and not only. From the point of view of the connections that can be established between this concept and the one regarding the staff management, we note the direct influence that the degree of motivation in the work, the commitment and the connection to the specific values of a certain organizational culture have on the performance of the subsidiary activities of the operations management. Effective operations management implies not only the optimal use of the organization’s resources, but also the engagement of staff through a behaviour whose specific features emphasize responsibility, teamwork, transparency, and commitment to assigned tasks. This article highlights the need for the staff to be connected as well as possible to the organization’s values and objectives; the efficient management of operations within it is closely connected to the level of harmonization between the values and objectives, on the one hand, and the interests and motivation of the employees, on the other hand.